THE NEXUS BETWEEN FINANCE AND ENTREPRENEURSHIP FOR THE NIGERIAN ECONOMIC GROWTH - Obamuyi, Tomola Marshal; Iriobe, Grace (Advances in Social Sciences Research Journal, 2018)
This study examined the nexus between finance and entrepreneurship for the Nigerian economic growth, using endogenous growth framework. Multivariate time series was employed to analyze the secondary data. Tests such as the unit root, co-integration and the vector error correction model were carried out for the empirical analysis. The normalised long-run co-integrating equation supported by the short-run dynamics showed that finance, entrepreneurship, interest rate, and industrial productivity are significant to economic growth in Nigeria. The paper concluded that the government should formulate effective macroeconomic policy targeted to entrepreneurship financing and growth. The paper further called for the overhauling of agencies and institutions set up for entrepreneurship to maximize the impact of entrepreneurial finance on the Nigerian economic growth.